Traps of Plebiscitary Decisions - Vinnykova, N. (BEROSTAV DRUŽSTVO, 2017)
The paper claims that spreading plebiscitary practices of political decision-making is not definitely an attribute of public engagement in policy-making processes, but more a sign of decline of representative democracy. Plebiscitary mechanisms of public participation, such as referendums, recalls and popular initiatives, instead of enhancing the democratic grade of political decision-making may transform into manipulative means of ensuring interests of elites in power or those, who are seeking for power. Involving illustrations based on the analysis of recent resonant precedents of plebiscitary decision-making, the article shows the most widespread traps of plebiscite public participation and their repercussions
EUROPEAN POLITICAL AND LAW DISCOURSE • Volume 4 Issue 2 2017. pp.21-30
Keywords: decision-making, participation, referendum, popular initiative, recall; Research Subject Categories::SOCIAL SCIENCES